On three new oonopid species from China and the discovery of the male Orchestina bialata Liu, Xiao & Xu, 2016 (Araneae: Oonopidae) - Liu, Keke; Henrard, Arnaud; Xiao, Yonghong; Xu, Xiang (Zootaxa, 2019)
Expeditions in the Jinggangshan National Nature Reserve in China yielded the discovery of some interesting goblin spiders (Oonopidae). Three new species of oonopid spiders are described and illustrated with photographs and SEMs: Ischnothyreus tergeminus sp. nov. (♂), Orchestina colubrina sp. nov. (♀), and O. zhiwui sp. nov. (♂). Both sexes of the species Orchestina bialata Liu, Xiao & Xu, 2016 were also collected and the male is described for the first time in this paper.